Contact exposure to neonicotinoid insecticides temporarily suppresses the locomotor activity of Pardosa lugubris agrobiont wolf spiders - Řezáč, Milan; Přibáňová, Gabriela; Gloríková, Nela; Heneberg, Petr (Scientific reports, 2022)
Exposure to numerous chemicals disrupts the spiders' locomotion. Spiders, particularly epigeic spiders, are dependent on their locomotory activities to search for prey, hide from their enemies, and perform sexual reproduction and subsequent parental care. Among the best-known compounds that inhibit the locomotion of arthropods are neonicotinoids. Despite spiders are less affected by the neonicotinoids than insects due to the sequence differences in their acetylcholine receptors, they are not resistant to these compounds. We hypothesized that acute exposure to a broad spectrum of neonicotinoids suppresses the traveled distance, mean velocity, and maximum velocity in epigeic spiders. As a model species, we used adults of Pardosa lugubris. We tested commercial formulations of thiamethoxam, acetamiprid, and thiacloprid. We tested each of the neonicotinoids in the maximum and minimum concentrations recommended for foliar applications. We applied them under controlled conditions dorsally by spraying them directly on the spiders or exposing the spiders to the tarsal contact with neonicotinoid residues. Control groups consisted of 31 individuals; treated groups consisted of 10-21 individuals. We found that a broad spectrum of neonicotinoids temporarily suppresses the traveled distance in epigeic spiders. At 1 h after application, all the three tested neonicotinoid insecticides induced declines in the traveled distance, but this effect mostly disappeared when tested at 24 h after the application. The decrease in the traveled distance was associated with substantial temporary decreases in the mean and maximum velocities. Despite differences among modalities, all three insecticides caused multiple adverse effects on the locomotory parameters in any tested concentrations. It remains to test what would be the lowest safe concentration for the chronic exposure to neonicotinoids in epigeic spiders.
Keywords: thiamethoxam; Thiamethoxam; insekticidy; Insecticides; Locomotion; zvířata; Nitro Compounds; dusíkaté sloučeniny; neonikotinoidy; lokomoce; Spiders; pavouci; Neonicotinoids; Animals